Synthesis, characterisation, and application of conjugated polyene modified TiO2 photocatalysts for the treatment of selected pharmaceuticals in water - Awofiranye, Olayinka Oladimeji Samuel (Vaal University of Technology, 2020)
This research has investigated the effects of conjugation on the visible light absorption capacity of polyene modified TiO2 nanoparticles as well as the efficiency of these nanoparticles for the mineralisation of acetaminophen (APAP), a non-antibiotic and chloramphenicol (CAP), an antibiotic pharmaceutical compound (PC) which are commonly used worldwide. The efficiency of polyene modified TiO2 (CPE-TiO2) compared with bare TiO2 was further assessed for the mineralisation of the selected PCs under visible light. To achieve this aim, the synthesised nanoparticles were appropriately characterised and tested for the photocatalytic degradation of acetaminophen (APAP) and chloramphenicol (CAP), under visible light. Furthermore, the mechanism and the kinetics of photocatalytic degradation of the PCs were investigated by using high-performance liquid chromatography (HPLC) to monitor the photodegradation intermediates, e.g. Hydroquinone, p-nitrophenol and oxamic acid. The DRS UV-vis spectra result of the CPE-TiO2 indicated that it has a lower band-gap than bare TiO2 nanoparticles and demonstrated a better absorption ability in the wavelength range of 400-800 nm. This result was further confirmed by other optical analyses, such as electrochemical impedance spectrometry (EIS) and photoluminescence (PL). The analysis indicated a less recombination rate of electron/hole pairs in CPE-TiO2 compared to TiO2. Notably, CPE-TiO2 nanocomposite exhibited higher photocatalytic properties for both pollutants, compared to bare TiO2 under visible light. Importantly, photocatalytic degradation experiments demonstrated that the CPE modified nanoparticles were significantly more efficient for PCs degradation (94.21 % for APAP and 80.47% for CAP) compared to bare TiO2 (27.12% for APAP and 36.12% for CAP). The role of CPE-TiO2 photocatalysis in degrading APAP and CAP was examined by varying experimental parameters such as PC concentrations, catalyst loading and solution pH. All the parameters were observed to influence the degradation of the PCs to some extent, albeit, at optimum conditions, most of these PCs were degraded within 210 minutes of visible light irradiation. A significant relationship between the ionic state (+ve or -ve based on the pH) of the solution and CPE-TiO2 photocatalytic process was observed. For the mineralisation, CPE-TiO2 photocatalysis led to higher oxidation rates compared to direct photolysis and bare TiO2 photocatalysis. The results confirm that the co-existence of multiple bonds in poly-conjugated carbon chains with a reduced band-gap in CPE-TiO2 composite were able to enhance charge separation and migration as well as improve the photocatalytic efficiency. This study has clearly demonstrated that polyene modified TiO2 nanoparticles can be applied to degrade PCs in aqueous solution and offers an attractive option for small-scale pharmaceutical wastewater treatment. However, the complex nature of real effluents with co-existing pollutants and higher levels of organic and inorganic matter may call for possible coupling of a biological process as pre- or post-treatment to improve their biodegradability.
Ph. D. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Polyene modified TiO2 nanoparticles; Pharmaceutical wastewater treatment; Antibiotic pharmaceutical compound (PC); Synthesised nanoparticles; Photocatalytic degradation of acetaminophen; Chloramphnicol; Dissertations, Academic -- South Africa.; Nanoparticles.; Pharmaceutical industry -- Waste disposal.; Sewage -- Purification -- Biological treatment.